2020
DOI: 10.1021/acsomega.0c04134
|View full text |Cite
|
Sign up to set email alerts
|

Time-Enhanced Performance of Oxide Thermoelectric Modules Based on a Hybrid p–n Junction

Abstract: The present challenge with all-oxide thermoelectric modules is their poor durability at high temperatures caused by the instability of the metal-oxide interfaces at the hot side. This work explains a new module concept based on a hybrid p−n junction, fabricated in one step by spark plasma co-sintering of Ca 3 Co 4−x O 9+δ (CCO, p-type) and CaMnO 3−δ /CaMn 2 O 4 (CMO, n-type). Different module (unicouple) designs were studied to obtain a thorough understanding of the role of the in situ formed hybrid p−n juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several groups have reported CaMnO3-based oxide thermoelectric modules where doped and un-doped CaMnO3 were used as n-type elements. Table 1 summarizes the perovskite CaMnO3-based thermoelectric module reported in the literature based on power output [71][72][73][74][75][76][77][78][79][80][81][82]. The thermoelectric module, in combination with CaMnO3 as an n-type element and Ca3Co4O9 or doped-Ca3Co4O9 as the p-type element, is the most efficient device reported to date.…”
Section: Perovskite Oxide-based Thermoelectric Modulementioning
confidence: 99%
“…Several groups have reported CaMnO3-based oxide thermoelectric modules where doped and un-doped CaMnO3 were used as n-type elements. Table 1 summarizes the perovskite CaMnO3-based thermoelectric module reported in the literature based on power output [71][72][73][74][75][76][77][78][79][80][81][82]. The thermoelectric module, in combination with CaMnO3 as an n-type element and Ca3Co4O9 or doped-Ca3Co4O9 as the p-type element, is the most efficient device reported to date.…”
Section: Perovskite Oxide-based Thermoelectric Modulementioning
confidence: 99%
“…Thermoelectric (TE) power generation offers an attractive route for the direct conversion of heat into electric power and is considered to be an important component of a sustainable future energy mix . Practical TE modules use p- and n-type semiconductors coupled together electrically in series and thermally in parallel . The performance of TE materials is estimated by the dimensionless figure of merit zT : Here, S (V/K) is the Seebeck coefficient, ρ (Ω·m) is the electrical resistivity, κ [κ el + κ lattic ] (W/m·K) is the thermal conductivity (sum of the electronic and lattice thermal conductivities), PF (W/m·K 2 ) is the power factor, and T ( K ) is the absolute temperature.…”
Section: Introductionmentioning
confidence: 99%
“…2 Practical TE modules use p-and n-type semiconductors coupled together electrically in series and thermally in parallel. 3 The performance of TE materials is estimated by the dimensionless figure of merit zT:…”
Section: Introductionmentioning
confidence: 99%
“…TEGs' structure and appropriate material combination also play an important role in improving their power output. Kanas reported an enhancement of a TEG's power output to 28.9 mW/cm 2 by improving the p-n junction and the cell design (Kanas et al, 2020). Lim reported a comparable power density of 93.2 mW/cm 2 in a TEG based on Ca3Co4O9, CaMnO3, and (Zn)7In2O3 materials and found that the contact resistance between electrode materials greatly affected the power output of the TEG in high-temperature regions (Lim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%